Presentation (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2021)
â€œVitruviusâ€™s Migrationsâ€ are the ideal continuations of the first issue on the theme of â€œGli ordini in architetturaâ€ edited by me for â€œLâ€™architettura delle cittÃ â€. As the title says, this issue is a collection of contributions dedicated to those visits, incursions, migrations in dramatically contemporary terms, which classical architecture and its logic of orders accomplished in other than traditional fields, be it for geographic and the relative cultural diversity, be it for diversity of expressive techniques, though oriented towards architecture, be it for exceptional opportunities for intervention that seemed to exclude recourse to those illustrious precedents. But always, as I observed in the editorial of â€œGli ordini in architetturaâ€ (Orders in Architecture) the center of interest is â€œthe search for the creation of meaning through architecture.â€ And, as corollary, it is the ability of classical tradition to become interpreter and answer to the expressive needs of the contemporary world.